EXPRESSION PATTERNS OF THE GLYCOGEN PHOSPHORYLASE GENE RELATED TO LARVAL DIAPAUSE IN Ostrinia furnacalis. Issue 4 (8th January 2016) - Guo, Jianqing; Zhang, Honggang; Edwards, Martin; Wang, Zhenying; Bai, Shuxiong; He, Kanglai
Abstract : Glycogen phosphorylase (GP) acts in the first step in release of glucose from glycogen, a form of energy storage for most organisms. To investigate the characteristics and expression pattern of GP gene ( Ofgp ) in the Asian corn borer, Ostrinia furnacalis (Guenée), larvae, we cloned and analyzed tissue transcription of Ofgp . The results indicate that the open reading frame (ORF) is 2, 526 bp, encoding 841 amino acid. The calculated three‐dimensional structure shows 33 α‐helices and 24 β‐sheets. Ofgp transcription levels varied significantly during the second to fifth instars under long‐day (28°C, 16:8 L:D photoperiod, and 70–80% relative humidity (RH)) and short‐day (24.5°C, 11:13 L:D photoperiod, and 70–80% RH) conditions, remained low during the prediapause phase, and then increased after about 36 d under short‐day photoperiod. In the larvae reared under long‐day condition, hemolymph ranked the highest in the transcript level of Ofgp . The highest transcription was recorded in the fat body and was lower in the other tissues in larvae reared under short‐day condition. We found that Ofgp transcription increased linearly from October 2012 to January 2013. The transcript level was negatively correlated with environmental temperature. We infer the higher Ofgp transcription may enhance the cold hardiness of the diapause larvae.